The Variability in Phonology of Indonesian Learner’s Interlanguage: A case study on English marked-fricatives - Fauzi, Iwan (Universitas Negeri Makassar, 2021)
Interlanguage is the most fruitful issue in the field of second language acquisition. In the interlanguage phase, Indonesian learners of English tend to alternate between two forms of language features to express the same language function where a variation of language forms will be exhibited to mark the variable of linguistic function. Variability in phonology of interlanguage is the most interesting subject to investigate based on markedness differential hypothesis theory. This study is aimed at finding out (1) marked sounds of English fricatives: [θ], [ð], [ʃ], and [ʒ] which are indicated as interlanguage variants; and (2) how interlanguage sound variants emerge based on surround the varying element. There were 30 college students of English study purposively selected to become respondents in this research representing advance and intermediate proficiency of English speaking. The data were taken from two types of task namely word list reading and sentence reading. There were 600-word tokens containing target marked sounds of fricative [θ], [ð], [ʃ], and [ʒ] obtained from the data collection. The analysis was done quantitatively to find the percentages of non-interlanguge sounds and interlanguge ones produced by respondents. The result showed that fricatives such as [θ], [ʃ], and [ʒ] have phonological variations in interlanguage with certain positions of word being pronounced. These phonological variations emerge due to the generalization of pronunciation by similar-ending sounds, the certain vowel sound preceding marked sounds, and the absence of consonant clusters in learners’ native language which bears the variation of certain marked fricatives of English.